Intradural Extramedullary Concurrent Schwannoma and Meningothelial Hyperplasia at C2-C3 Cervical Vertebrae: A Case Report and Review of Literature - Rayan Rammal; Daniel F. Marker; Rana Naous (Case Reports in Pathology)
Concomitant schwannomas and benign meningothelial proliferations, including meningothelial hyperplasia or meningioma, rarely occur at the same location outside the setting of neurofibromatosis. Herein, we present a rare case of concurrent schwannoma and benign meningothelial hyperplasia concomitantly occurring in the cervical spine of a 69-year-old male patient with no history of any genetic disorder.